Under phosphate starvation conditions, Fe and Al trigger accumulation of the transcription factor STOP1 in the nucleus of Arabidopsis root cells. (4th June 2019) - Godon, Christian; Mercier, Caroline; Wang, Xiaoyue; David, Pascale; Richaud, Pierre; Nussaume, Laurent; Liu, Dong; Desnos, Thierry
Summary: Low‐phosphate (Pi) conditions are known to repress primary root growth of Arabidopsis at low pH and in an Fe‐dependent manner. This growth arrest requires accumulation of the transcription factor STOP1 in the nucleus, where it activates the transcription of the malate transporter gene ALMT1 ; exuded malate is suspected to interact with extracellular Fe to inhibit root growth. In addition, ALS3 – an ABC‐like transporter identified for its role in tolerance to toxic Al – represses nuclear accumulation of STOP1 and the expression of ALMT1 . Until now it was unclear whether Pi deficiency itself or Fe activates the accumulation of STOP1 in the nucleus. Here, by using different growth media to dissociate the effects of Fe from Pi deficiency itself, we demonstrate that Fe is sufficient to trigger the accumulation of STOP1 in the nucleus, which, in turn, activates the expression of ALMT1 . We also show that a low pH is necessary to stimulate the Fe‐dependent accumulation of nuclear STOP1. Furthermore, pharmacological experiments indicate that Fe inhibits proteasomal degradation of STOP1. We also show that Al acts like Fe for nuclear accumulation of STOP1 and ALMT1 expression, and that the overaccumulation of STOP1 in the nucleus of the als3 mutant grown in low‐Pi conditions could be abolished by Fe deficiency. Altogether, our results indicate that, under low‐Pi conditions, Fe 2/3+ and Al 3+ act similarly to increase the stability of STOP1 and its accumulation in the nucleus where it activates the expression of ALMT1 . Significance Statement: Low‐phosphate, low‐pH and excess aluminum are three major stresses inhibiting root growth. The Arabidopsis transcription factor STOP1 has a major role in root growth under these different stresses, but how STOP1 is regulated is not known. Here we show that Fe –instead of low‐phosphate– and Al promote the accumulation of STOP1 in root nuclei, in a low‐pH‐dependent manner. This work unveils an important regulatory step in the response to Al and Fe stresses.